Pendekatan Sintaksis dalam Analisis Kesalahan Berbahasa Mahasiswa - Nurul Asa; Puput Adelina Sianturi; Putri Ayu Adelina Situmorang; Windi Aura; Anggia Puteri; Frina Lestarina Barus (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to identify and analyze syntactic errors made by students in their academic writing. Using a descriptive qualitative approach, this study explores in depth the forms of errors that appear and the general patterns formed in students' sentence structures. Data were obtained from various documents of students' academic writing, such as essays, papers, and observation reports. The results of the study indicate that the dominant syntactic errors include incomplete sentence construction, inappropriate use of conjunctions, the influence of regional languages in sentence structures, inaccuracy in phrase formation, and errors in the structure of subjects, predicates, and objects. These findings reflect students' weak mastery of Indonesian language syntax rules. Therefore, more effective learning strategies are needed, such as the use of discovery-based learning methods and providing direct feedback, to improve students' syntactic competence. Syntactic error analysis not only functions as an evaluation of language skills, but also as a basis for developing contextual and relevant teaching materials.